Design Of A Mobile-Based Information System For Service Ordering At Teguh Design Printing And Screen Printing Services - Mahfudz, Muhammad Syah Farros; Mutiara Handayani Ujianti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study aims to design a mobile-based information system for service ordering at Teguh Design, a printing and screen-printing business. The primary issue identified is the absence of an effective information system, as current ordering processes rely on manual methods, leading to potential data loss and record-keeping errors. Data collection methods included direct observation of the existing system, interviews with stakeholders, and a literature review to support analysis. The findings reveal that the current ordering system is inefficient and prone to errors, impacting customer satisfaction and company performance. Consequently, the implementation of a structured, mobile-based information system is essential to enhance operational efficiency and service quality. With the new system, orders can be placed online, allowing customers to make reservations more easily and quickly. Additionally, the system will improve data management, ensuring greater accuracy and security. Recommendations include employee training, regular monitoring and evaluation, and collaboration with relevant stakeholders to optimize system development. These steps are expected to enhance Teguh Design's competitiveness in the market.